Evaluation of Mindray BC‐3600 hematology analyzer in a university hospital. Issue 1 (23rd August 2012) - Shu, G.; Lu, H.; Du, H.; Shi, J.; Wu, G.
Summary Introduction The BC‐3600 Auto Hematology Analyzer (hereinafter call BC‐3600) is a quantitative, automated hematology analyzer and leukocyte differential counter for In Vitro Diagnostic Use in clinical laboratories. Methods The analyzer was evaluated and compared with the Mindray BC‐3200 3‐part differential (BC‐3200) and Sysmex XE‐2100 5‐part differential (XE‐2100) Hematology Analyzer in the hematology laboratory of a university hospital. The BC‐3600 was evaluated according to guidelines published by Clinical and Laboratory Standards Institute (CLSI), the International Committee for Standardization in Hematology (ICSH), and Department of Food and Drug Administration (FDA). Results There were no background, minimal carryover (<0.5%), and excellent linearity for white blood cell (WBC), hemoglobin (Hb) level, red blood cell (RBC), and platelet (PLT) counts (r > 0.999). Precision was good at all levels for the routine cell blood count (CBC) parameters: CV% being ≤2.0, except for platelet count (PLT) at the low level with CV% of ≤5.0% and WBC at the low level with CV% of <3.0%. Correlation between the BC‐3600 and BC‐3200, XE‐2100 were excellent (r > 0.99) for all major CBC parameters. Conclusion It is concluded that the overall performance of the BC‐3600 is excellent and compares well with that of BC‐3200 and XE‐2100.